Local Financial Management and Local Asset Management Treatment of the Regional Financial and Asset Management Agency (BPKAD) of Lamongan Regency - Sujarwo Arif Efendi; Abid Muhtarom; Ratna Handayati; Abidah Dwi Rahmi (Sean Institute, 2026)
This research aims to analyze the influence of Local Financial Management and Local Asset Management of the Regional Financial and Asset Management Agency (BPKAD) of Lamongan Regency, both simultaneously and partially. This research uses a qualitative approach, namely explaining phenomena in depth through data collection. The population in this research are informants who have knowledge, responsibility and direct involvement in regional financial and asset management within the Lamongan Regency Regional Financial and Asset Management Agency (BPKAD), with a total sample of 6 people. The data analysis technique used goes through several stages as follows: data reduction, data display, and conclusion/verification. The research results show that the main supporting factors for regional financial and asset management in Lamongan Regency include human resource competence, good accounting and reporting systems, thorough planning and budgeting, and adequate information technology support. Meanwhile, inhibiting factors include limited human resources who understand accrual-based systems, disorderly asset inventory, and weak cash flow management and coordination between regional organizations. In general, management of regional finances and assets in Lamongan Regency has been running effectively, but there is still a need to improve aspects of data management and strengthening the integrity of the apparatus to achieve regional fiscal independence.